Role of Sm3+ ions as network-modifying on elastic, mechanical, and radiation shielding properties of MgO–B2O3–TeO2 glasses - Zalamin, S.N.F.; M Zaid, M.H.; Matori, K.A.; Karim, M.K.A.; Yaakob, Y.; Cheong, W.M.; Loh, Z.W.; Sayyed, M.I. (Elsevier, 2023)
A series of samarium doped magnesium borotellurite glass with empirical formula (60-)TeO2–30B2O3–10MgO– (Sm2O3) was produced via melt-quenching technique, with x is varied to 0.0, 0.5, 1.0, 2.0 and 3.0 mol. The bulk density of the Sm-doped MBT glass was increased from 4.105 g/cm3 to 4.403 g/cm3 by adding samarium oxide. Besides, the molar volume illustrated a contrary trend with the decreasing range from 29.39 cm3/mol to 28.69 cm3/mol. XRD analysis proves the amorphous state of glasses and elastic moduli demonstrated a linear increase with the increment of Sm2O3. The longitudinal modulus, L, varies between 60.57 and 73.24 GPa, whereas Young's modulus, E, changes from 50.83 to 61.92 GPa. In addition, the bulk modulus, K, varies between 33.37 and 40.00 GPa, and the shear modulus, G, ranges between 20.39 and 24.93 GPa. The Poisson's ratio values were noted to be between 0.236 and 0.246. Furthermore, the microhardness increase in the range of 5.35–6.61 GPa. The elastic moduli from the Makishima-Mackenzie model followed the same trend as the experimental values. For theoretical evaluation of the shielding properties, the Phy-X program was used. The results show that the MBTGSm3.0 glass sample currently has the highest shielding properties due to the addition of Sm2O3 to the glass structure, indicating that the glass sample was suitable for radiation glass shielding applications.